Evaluating the Journalism and Political Identity of an Intellectual: Asım Us and the Newspaper Kurun (1935–1939) - Volkan Payaslı (Yakın Dönem Türkiye Araştırmaları)
Asım Us, who has left deep traces in Turkish press life with his half-century-old columns, was able to read Turkish foreign policy well and wrote articles based on universal law, thanks to the education he received during the years of Mülkiye School. He asked the Turkish people to unconditionally adhere to Atatürk, his principles and reforms, as well as to his party. The main problematic of this study is the evaluation of the events that shaped domestic and foreign politics in Türkiye through his views. The article is an analysis of what Asım Us saw, heard and remembered. The main titles of this study are based on the articles he wrotein the period 1935-1939 and the headlines reflected in Kurun. The 1935 elections, women’s acquisition of the right of representation in the parliament, the Fourth Great Congress of the Republican People’s Party (CHP), the change of the Straits regime in favor of Türkiye, Hitler’s Germany and the Hatay issue constitute the main axis of the article. This study tries to eliminate the deficiency in the literature by making use of the Presidency Archives, The Directorate of State Archives of the Presidency of the Republic of Türkiye: The Departments of the Ottoman and Republic Archives.